1999
DOI: 10.1159/000029851
|View full text |Cite
|
Sign up to set email alerts
|

Release of Amino Acids, Fluorescamine-Reactive Substances and Substance P from the Epidermis of the Living Animal

Abstract: The present study demonstrates a procedure for extraction and determination of stratum corneum amines in the living animal. A nonleaky well, containing 10 mM Tris-HCl buffer, pH 7.0, was constructed on the shaved backs of anesthetized animals. It was found that Ser, Ala, Gly and Pro are mainly released from the stratum corneum of 4-month-old guinea pigs, and in 2-month-old rats, Gly, Ser and Arg show the highest degree of release. Much lower amino acid concentrations were observed in 20-month-old rats. This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We have shown that substance P is released from skin terminals upon exposure to high temperature and exposure to the alkylating agent nitrogen mustard (8). It was assumed that substance P is involved in the initiation of the inflammatory process, leading to the erythema, edema and finally to blister and ulceration.…”
Section: Mechanism Of the Protective Activity Of Iodinementioning
confidence: 99%
“…We have shown that substance P is released from skin terminals upon exposure to high temperature and exposure to the alkylating agent nitrogen mustard (8). It was assumed that substance P is involved in the initiation of the inflammatory process, leading to the erythema, edema and finally to blister and ulceration.…”
Section: Mechanism Of the Protective Activity Of Iodinementioning
confidence: 99%